Logika Desain Pesan pada Konten Dakwah Akun Instagram @cerita.jarrah - Safarina, Witriani Siti; Wahyudin, Aep; Nase, Nase (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study aims to determ; a) expressive logic in messages on the da'wah content of the @cerita.jarrah Instagram account, b) conventional logic in messages on the da'wah content of the @cerita.jarrah Instagram account, c) rhetorical logic in messages on the da'wah content of the @cerita.jarrah Instagram account. The research method used is descriptive qualitative method, which includes observation, interview, and document analysis. The theory used is the theory of message design logic proposed by O'Keefe about different ways of thinking in shaping a message. The da'wah content on @cerita.jarrah displays the characteristics of expressive logic is designed with non-formal language and focusing on the emotional aspects and desires of the communicator. Meanwhile, conventional logic is the inclusion of Quranic verses, Hadith, or character quotes. Messages that use rhetorical logic are generally in the form of slogans and use cause and effect patterns.